Preload responsiveness in patients with acute respiratory distress syndrome managed with extracorporeal membrane oxygenation - Loosen, Gregor; Conrad, Alice; Essert, Nils; Bösing, Christoph; Hagmann, Michael; Thiel, Manfred; Luecke, Thomas; Rocco, Patricia R. M.; Pelosi, Paolo; Krebs, Jörg (ASAIO journal, 2024)
A restrictive fluid strategy is recommended in patients with acute respiratory distress syndrome (ARDS) managed with venovenous extracorporeal membrane oxygenation (VV ECMO). However, there are no established predictors for preload responsiveness in these patients. In 20 ARDS patients managed with VV ECMO, transesophageal echocardiography was used to repeatedly evaluate dynamic parameters of the left (velocity and stroke volume variation) and right ventricular outflow tract (velocity [respiratory variations of the maximal Doppler velocity in the truncus pulmonalis {ΔVmaxTP}] and velocity time integral [respiratory variation of the velocity time integral measured in the truncus pulmonalis {ΔVTI_TP}] variation in the truncus pulmonalis), the diameter variation in the superior and inferior vena cava and stroke volume variation measured by pulse contour analysis (SVV_PCA). Patients were categorized as responders and nonresponders according to an increase in stroke volume measured by echocardiography during a Passive Leg Raise Test with a cutoff value ≥10%. The final analysis includes 86 measurements. Predictive values for preload responsiveness were found for ΔVmaxTP (area under the curve [AUC] of 0.64), ΔVTI_TP (AUC 0.67), and SVV_PCA (AUC 0.74). In conclusion, SVV_PCA and, to a lesser extent, ΔVmaxTP and ΔVTI_TP are the most accurate parameters to predict preload responsiveness in ARDS patients managed with VV ECMO. Transesophageal echocardiography offers no advantages over pulse contour analysis for predicting preload responsiveness and provides only intermittent monitoring and assessment.
Gesehen am 04.04.2024